Patroni ulic i placów w miasteczku akademickim Uniwersytetu Warmińsko-Mazurskiego w Kortowie - Joanna Maria Garbula, Joanna Maria Garbula (Biuletyn Historii Wychowania, 2019)
This article revolves around the memory of a site, i.e. the past captured in sources, reported memories of witnesses of events and symbols. The examples of such places of memory examined here are the streets and squares on the UWM Kortowo campus. They consist of references to the past which has significance for contemporary times. The article consists of an introduction and two chapters. The introduction presents the rich history of Kortowo, spanning several centuries from the Old Prussian settlements to the establishment of the University of Warmia and Masuria in Olsztyn. Chapter 1 is dedicated to the history of the streets and squares on the Kortowo campus from the time when, to make the academic community’s life easier, the university authorities gave names to the streets on the campus, following the specific faculties’ suggestions. The streets were named after M. Oczapowski (an agronomist, theorist of agriculture, pioneer of agricultural experimentation), R. Prawocheński (an expert in animal husbandry), J. Licznerski (a pioneer of modern dairy science), K. Obitz (Doctor of veterinary medicine, a journalist, a social activist in Masuria), J. Hevelius (an astronomer from Gdansk), B. Dybowski (a biologist and traveller), C. Kanafojski (Professor of automation in agriculture). Chapter 2 presents short biographies of three of the seven street patrons: B. Dybowski, K. Obitz and R. Prawocheński, who are the most characteristic and multi-dimensional figures. The names of the streets reflect the memory of the scientific, social and personal achievements of these individuals, at the same time justifying their selection as patrons.